1940
DOI: 10.1063/1.1750585
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Solution of Metals in Acids as a Function of Overvoltage I. The Diffusion Potential

Abstract: The problem of simultaneous conduction and diffusion through a constrained diffusion layer is discussed. An exact solution is obtained for the case of an ideal dilute solution containing only two ionic species. The special case of divalent ions diffusion into a uni-divalent electrolyte is also solved by numerical methods. It is shown that for diffusion layers of thicknesses of the order of 50μ the potential drop across the layer for currents of the order of magnitude of 100 milliamperes per sq. cm is less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1949
1949
1978
1978

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Lyklema et al (20) demonstrated several aspects of nonequilibrium behavior at glass electrodes. In view of the success of kinetic theories in treating corrosion processes, it seems that the relationships developed for mixed potentials at zero current by various workers (21)(22)(23) could be fruitfully applied to ion-selective membrane electrodes. We have demonstrated that relationships originally developed for metal electrodes are approximately valid for ion-selective membrane electrodes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Lyklema et al (20) demonstrated several aspects of nonequilibrium behavior at glass electrodes. In view of the success of kinetic theories in treating corrosion processes, it seems that the relationships developed for mixed potentials at zero current by various workers (21)(22)(23) could be fruitfully applied to ion-selective membrane electrodes. We have demonstrated that relationships originally developed for metal electrodes are approximately valid for ion-selective membrane electrodes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Once the "characteristics", i.e., the straight lines associated with the critical points, have been found, it is an easy matter, knowing equation (III), to give the main features of a transient corresponding to any values of E and R. 5 Under similar circumstances, the potential drop across the diffusion layer has been deduced to be negligible. See reference (9).…”
Section: Prediction Of General Features Of a Make Transient-mentioning
confidence: 99%
“…Kozlowski (32) already successfully applied the mixed potential theory (25,26) used in corrosion research to amalgam electrodes which can be viewed as standing between metal electrodes and ion-selective electrodes. It is therefore justified to describe ion-selective electrodes also from this point of view.…”
Section: Concerning the Selectivity Coefficient Defined In An Extendedmentioning
confidence: 99%
“…For this the theory predicts a mixed potential located in between both the equilibrium potentials. In this model (25,26), the location of the mixed potential depends on the thermodynamic parameters (equilibrium potentials) as well as on the kinetic parameters (exchange current densities) according to Equation 11.27 of (27). The establishment of a thermodynamic equilibrium may be prevented for one or both reactions, depending on the course of the interacting current-voltage curves.…”
mentioning
confidence: 99%